Answer: f(n) + g(n) = -2n^3 + 3n^2 – 2n – 4 Step-by-step explanation: Honestly i dont know if that answer is correct im just trying to gain points but i copied it from someone else 2n +5y=6 eggs Log in to Reply

Answer: f(n) + g(n) = -2n^3 + 3n^2 – 2n – 4 Explanation: f(n) + g(n) = (-2n^3 + 3n^2) + (-2n – 4)f(n) + g(n) = -2n^3 + 3n^2 – 2n – 4 Log in to Reply

Answer: f(n) + g(n) = -2n^3 + 3n^2 – 2n – 4

Step-by-step explanation:

Honestly i dont know if that answer is correct

im just trying to gain points

but i copied it from someone else

2n +5y=6 eggs

Answer: f(n) + g(n) = -2n^3 + 3n^2 – 2n – 4

Explanation:

f(n) + g(n) = (-2n^3 + 3n^2) + (-2n – 4)

f(n) + g(n) = -2n^3 + 3n^2 – 2n – 4